Apomorphine and psychopathology. Issue 7 (July 1975) - Lal, S; De la Vega, C E
Abstract : Forty men, mainly alcoholics, were administered either the dopamine receptor agonist, apomorphine HCl (1 mg), or distilled water subcutaneously three times a day for 14 days in a double blind study. None of the subjects developed an endogenous depression or schizophrenic symptoms. Scores on the Hamilton Rating Scale, Zung Self Rating Scale, and Brief Psychiatric Rating Scale showed improvement with both apomorphine and placebo. There were no significant differences between the two treatments on these rating scales. A significant incidence of spontaneous penile erections occurred after apomorphine treatment compared with placebo. Both treatments eliminated subjective craving for alcohol. Acute administration of apomorphine had no effect on psychomotor retardation or depressed mood in two patients with endogenous depression.